1984
DOI: 10.1210/jcem-59-5-1025
|View full text |Cite
|
Sign up to set email alerts
|

BLOCKADE OF hp-GRF-40-INDUCED GH RELEASE IN NORMAL MEN BY A CHOLINERGIC MUSCARINIC ANTAGONIST

Abstract: In five healthy young men, pretreatment with the cholinergic muscarinic antagonist pirenzepine (0.6 mg/kg iv) almost completely abolished the rise in plasma growth hormone (GH) elicited by an iv bolus injection of 1 microgram/kg human pancreatic GH-releasing factor 1-40 (hp-GRF-40). These data demonstrate that cholinergic receptor sites involved in GH-releasing mechanisms do not interact with GRF-secreting structures in the central nervous system. A mechanism mediated via hypothalamic release of somatostatin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 7 publications
4
36
0
Order By: Relevance
“…Pirenzepine is a mus carinic cholinergic antagonist that blocks the GH response to a variety of stimuli, but not insulin-induced hypoglycaemia [9][10][11]. Our finding of partial blockade of the GH response to GHRH by pirenzepine supports an earlier re port [22], as well as a more recent study by Casanueva et al [5] using atropine. As pirenzepine only poorly penetrates the blood-brain barrier [15], ant there is no evidence for a direct cholinergic modulation of pituitary GH release [3.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pirenzepine is a mus carinic cholinergic antagonist that blocks the GH response to a variety of stimuli, but not insulin-induced hypoglycaemia [9][10][11]. Our finding of partial blockade of the GH response to GHRH by pirenzepine supports an earlier re port [22], as well as a more recent study by Casanueva et al [5] using atropine. As pirenzepine only poorly penetrates the blood-brain barrier [15], ant there is no evidence for a direct cholinergic modulation of pituitary GH release [3.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have demonstrated that the release of serum GH induced by GHRH( I -40) is attenuated by pirenzepine. a cholinergic muscarinic antagonist [22], while proprano lol enhances the rise in serum GH in response to GHRH(I-44)NH; [6]. Shortened analogues of GHRH may also stimulate GH release, and it has been demonstrated that GHRH( I -29) NH: is equipotent to both GHRH( I -40) and GHRH( l-44)NH; on a weight basis [14,21].…”
mentioning
confidence: 99%
“…Thus, in humans atropine, a muscarinic cholinergic antagonist, or PZ, a more selective antagonist of muscarinic M1 receptors (Watson et al 1983), were able to suppress the GH release elicited by insulin hypoglycemia (Blackard & Waddel 1969), arginine (Casanueva et al 1984) or GHRH (Massara et al 1984), while conversely, pyridostigmine, an acetylcholinesterase (Ach-E) inhibitor, greatly enhanced the GH release elicited by GHRH , Ross et al 1987. Studies in both animals (Torsello et al 1988) and humans (Ross et al 1987) have also disclosed an important cholinergic link in the feedback action of GH, involving SS release.…”
Section: Discussionmentioning
confidence: 99%
“…The selective block of muscarinic receptor blunts the GH release induced by a variety of stimulations [9,11,25,26]. It might be recalled that in another situation, namely anorexia nervosa, pirenzepine fails to antagonize GHRH in the stimulation of GH [27],…”
Section: ]mentioning
confidence: 99%
“…Cholinergic agents or cholinergic tonus enhancement by cholinesterase inhibitors enhance GH serum levels in humans [7,8] and GH response to differ ent stimulatory agents, including GH-releasing hormone (GHRH) [8], Since atropine [9. 10] and pirenzepine [11], but not nicotine [10] block these effects, a muscarinic receptor is thought to be involved.…”
Section: Introductionmentioning
confidence: 99%